The making of Japanese settler colonialism : Malthusianism and trans-Pacific migration, 1868-1961 - Lu, Sidney Xu, 1981- (Cambridge : Cambridge University Press, 2019)
This innovative study demonstrates how Japanese empire-builders invented and appropriated the discourse of overpopulation to justify Japanese settler colonialism across the Pacific. Lu defines this overpopulation discourse as'Malthusian expansionism'. This was a set of ideas that demanded additional land abroad to accommodate the supposed surplus people in domestic society on the one hand and emphasized the necessity of national population growth on the other. Lu delineates ideological ties, human connections and institutional continuities between Japanese colonial migration in Asia and Japanese migration to Hawaii and North and South America from 1868 to 1961. He further places Malthusian expansionism at the center of the logic of modern settler colonialism, challenging the conceptual division between migration and settler colonialism in global history. This title is also available as Open Access.
Introduction: Malthusian expansion and settler colonialism : Japan in global history -- Japanese settler colonialism in Hokkaido and North America and the rise of Malthusian expansionism -- Chinese exclusion in the U.S. and the Japanese expansion to the South Seas, Hawai'i and Latin America -- The First Sino-Japanese War and the Japanese labor migration to the U.S. -- Japanese rice cultivation in Texas and the paradigm shift of Malthusian expansionism --'Carrying the white man's burden' : the Japanese American enlightenment campaign and the rise of Japanese farmer migration to Brazil -- The marriage of Malthusian expansionism and Japanese agrarianism and the creation of the migration state -- Nagano migration and the illusion of co-existence and co-prosperity in Japanese settler colonialism in Brazil and Manchuria -- The resurgence of Japanese migration to South America and the decline of Malthusian expansionism -- Conclusion: Re-thinking migration and settler colonialism in the modern world.
Title from publisher's bibliographic system (viewed on 26 Jul 2019).
Keywords: Japan -- Colonies -- History -- 19th century; Japan -- Colonies -- History -- 20th century; Japan -- Emigration and immigration -- History -- 19th century; Japan -- Emigration and immigration -- History -- 20th century; Malthusianism; Demographic transition -- Japan; Japan -- Foreign relations -- 1868-